2016
DOI: 10.1038/mp.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

DISC1 causes associative memory and neurodevelopmental defects in fruit flies

Abstract: Originally found in a Scottish family with diverse mental disorders, the DISC1 protein has been characterized as an intracellular scaffold protein that associates with diverse binding partners in neural development. To explore its functions in a genetically tractable system, we expressed the human DISC1 in fruit flies (Drosophila melanogaster). As in mammalian neurons, DISC1 is localized to diverse subcellular domains of developing fly neurons including the nuclei, axons and dendrites. Overexpression of DISC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 83 publications
(127 reference statements)
3
18
0
Order By: Relevance
“…Nonetheless, the biological impact of DISC1 deficits in the Scottish pedigree is not yet perfectly understood. We have reported that transgenic Drosophila expressing wildtype (WT) human DISC1 in the mushroom body (a gain of function model) show several abnormalities, including disturbance in sleep homeostasis (Sawamura et al, 2008; Furukubo-Tokunaga et al, 2016). Here we generated transgenic mice that express WT human DISC1.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the biological impact of DISC1 deficits in the Scottish pedigree is not yet perfectly understood. We have reported that transgenic Drosophila expressing wildtype (WT) human DISC1 in the mushroom body (a gain of function model) show several abnormalities, including disturbance in sleep homeostasis (Sawamura et al, 2008; Furukubo-Tokunaga et al, 2016). Here we generated transgenic mice that express WT human DISC1.…”
Section: Introductionmentioning
confidence: 99%
“…The following observations support this contention. First, dysbindin interacts with DISC1 at the synapse (Furukubo‐Tokunaga et al, ). DISC1 is a gene mutated in neuropsychiatric and neurodevelopmental disorders, and it is required for neuronal development and synapse function (Blackwood et al, ; Kilpinen et al, ; Crepel et al, ; Porteous et al, ; Wen et al, ).…”
Section: Neurodevelopmental Disorders Associated To Bloc‐1 and Borc Cmentioning
confidence: 99%
“…The following observations support this contention. First, dysbindin interacts with DISC1 at the synapse (Furukubo-Tokunaga et al, 2016a, 2016b. DISC1 is a gene mutated in neuropsychiatric and neurodevelopmental disorders, and it is required for neuronal development and synapse function Figure 3 Deleterious mutations in genes from BLOC-1, BORC, and primary cilia interactomes in schizophrenia patients.…”
Section: Neurodevelopmental Disorders Associated To Bloc-1 and Borc Cmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze genetic interactions of DISC1 and psychiatric risk factor genes, we have introduced the human DISC1 gene in fruit flies to be expressed in their nervous system. We showed previously 27 that overexpression of DISC1 ( DISC1 OE ) suppresses synaptogenesis at the developing larval NMJs. In this work, we conducted a systematic screening for interacting risk factor genes that cooperatively function with DISC1 to cause modification of the synaptic phenotypes.…”
Section: Introductionmentioning
confidence: 98%